2011
DOI: 10.1177/1354856510394593
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Nature of Public Service Radio: A Case Study of iCat fm

Abstract: In an openly hostile environment in which public service broadcasting (PSB) has to justify its mere existence, its relationship with new technologies and its transformation into Public Service Media (PSM) have been the subject of controversy in Europe, with respect to the legitimate use of new technologies by a public broadcasting service. Making use of qualitative techniques with a case study, this article illustrates how the Catalan public broadcaster iCat fm uses diverse technological distribution platforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 7 publications
1
10
0
2
Order By: Relevance
“…This is true for the CCMA (Corporació Catalana de Mitjans Audiovisuals), the organisation that, according to most of the interviewees, has pioneered many of the innovations introduced by Spanish broadcasters. This vision from practitioners is consistent with scholarly research, which in the last decade has demonstrated the innovative approach of this organisation to the new scenario characterised by digitalisation, convergence and the development of new applications (Bech et al, 2010;Bonet, M., Fernández-Quijada, D., & Ribes, X., 2011;Fernández-Quijada & Fortino, 2009;Medina et al, 2011;Prado & Fernández, 2006). CCMA managers admit that they have been able to promote an "innovation culture" within the organisation that even has led to "a line where you're rapidly criticised when you don't innovate" (content manager, CCMA).…”
Section: Analysis: How Psm Manage Innovationsupporting
confidence: 62%
See 1 more Smart Citation
“…This is true for the CCMA (Corporació Catalana de Mitjans Audiovisuals), the organisation that, according to most of the interviewees, has pioneered many of the innovations introduced by Spanish broadcasters. This vision from practitioners is consistent with scholarly research, which in the last decade has demonstrated the innovative approach of this organisation to the new scenario characterised by digitalisation, convergence and the development of new applications (Bech et al, 2010;Bonet, M., Fernández-Quijada, D., & Ribes, X., 2011;Fernández-Quijada & Fortino, 2009;Medina et al, 2011;Prado & Fernández, 2006). CCMA managers admit that they have been able to promote an "innovation culture" within the organisation that even has led to "a line where you're rapidly criticised when you don't innovate" (content manager, CCMA).…”
Section: Analysis: How Psm Manage Innovationsupporting
confidence: 62%
“…tence (Jacka, 2003) or its unlikely future (Tracey, 1998), most of them are in favour of an active role of these broadcasters (Brevini, 2010;Debrett, 2009;Suárez Candel, 2012), as reflected in specific case studies (Van den Bulck, 2008;Whittle, 2004), including Spain (Bonet, Fernández-Quijada, & Ribes, 2011;Prado & Fernández, 2006), the home country of the organisations analysed in this study.…”
mentioning
confidence: 94%
“…Some of these public stations are attempting to curb the escape of the prized young age range through custom-made offers of FM and digital thematic networks (BBC Six in the United Kingdom, Le Mouv' in France, Radio Tres in Spain, Radio Wave in the Czech Republic) and with an increased presence on social networking websites. A prime example is the Catalan regional station iCat which, as Bonet (in Bonet et al 2011) affirms, has successfully repositioned its format based on the paradigm of The Long Tail (C. Anderson, 2007) and on the offer of different content on different platforms. All the success stories in public service lie in the theming and the investment of resources into the development of technological platforms.…”
Section: Public Service Radio: In Search Of Legitimation Through Socimentioning
confidence: 99%
“…Sin embargo, en Internet la esencia de la radio musical basada en la prescripción y la participación del oyente se mantiene a través del podcast (Sellas, 2012) y el uso cada vez más frecuente de las redes sociales (Bonini et al, 2015). De este modo, los servicios de música en streaming pueden ser una buena manera de redondear esta presencia de la radio en la Red para atrapar a unos oyentes cada vez más escasos además de perfeccionar el cumplimiento de su función de servicio público, a menudo poco resaltada en detrimento de la información (Bonet et al, 2011). Así, este objeto de estudio se aborda desde la perspectiva del servicio público que se presupone a los medios públicos y es por ello que no hemos abordado a la radio musical privada.…”
unclassified